Distribution of Staphylococcus species in dairy cows, workers and shared farm environments. Issue 15 (14th June 2018) - Roberts, Marilyn C; Garland-Lewis, Gemina; Trufan, Sally; Meschke, Scott J; Fowler, Heather; Shean, Ryan C; Greninger, Alexander L; Rabinowitz, Peter M
Abstract: Dairy farming involves frequent contact among animals, workers and farm environments. To explore the Staphylococcus spp. diversity that occurs on dairy farms, a pilot study sampled dairy workers, cows and the farm environments from five farms, two organic and three conventional farms, in Washington State. Samples were taken from the nares and hands of consenting workers (n = 24), udders and nares of selected cows (n = 25) and representative environmental surfaces (n = 96) from each farm. To increase diversity of the Staphylococcus spp. characterized, five distinct colonies were selected from each sample for identification with 16S analysis. A total of 198 staphylococci were characterized representing 19 different Staphylococcus spp. The diversity of species ranged from 9–15 Staphylococcus spp./farm with no difference between conventional and organic farms. S. haemolyticus [n = 60 isolates] was the most common species and was isolated from all farms and from cows, humans and environmental samples. Whole genome sequencing of selected S. haemolyticus found no genetically related isolates among human, animal and environmental samples within the same farm. S. epidermidis, S. saprophyticus, S. sciuri and S. xylosus were also found in ≥1 farms from human, animal and environmental samples. Abstract : The study took a "One Health" approach by examining staphylococci in humans, animals, as well as, the environment, in order to better understand the interactions of microbial communities and the possible impact of such interactions.